In vitro evaluation of topical gel prepared using silk fibroin at different concentration of gel accelerating agent- Glycerol - A. LOKHADE,; S. BIRADAR,; A. PARADKAR,; K. MAHADIK, (International Journal of Pharma and Bio Sciences, 2011)
The pharmaceutical utility of silk fibroin as a possible material for wound healing was investigated. Topical Silk fibroin gel (SFG) was prepared from its aqueous solution. The rate of gelation was sufficiently accelerated by addition of glycerol to silk fibroin (SF) aqueous solution. Rheological properties of topical SFG were evaluated using controlled stress rheometer. The glycerol content affected the spreadability, extrudability, bioadhesivity, linear viscoelastic region (LVR), tan δ, and creep recovery of topical SFG. It was found that topical SFG was able to prepare at room temperature (20 ± 5â—¦C).